There is no Planet B : a handbook for the make or break years - Berners-Lee, Mike, 1964- (Cambridge University Press, 2020)
"Mike Berners-Lee thinks, writes, researches and consults on sustainability and responses to the challenges of the twenty-first century. He is the founder of Small World Consulting (SWC), an associate company of Lancaster University, which works with organisations from small businesses to the biggest tech giants. SWC is a leader in the field of carbon metrics, targets and actions"--